2018
DOI: 10.1080/1828051x.2018.1423583
|View full text |Cite
|
Sign up to set email alerts
|

Effect of transport length and genotype on tonic immobility, blood parameters and carcass contamination of free-range reared chickens

Abstract: The aim of the present study was to investigate the effect of transport on welfare traits, several haematological parameters and carcase hygiene in two different chicken genotypes (fast-and slow-growing strains) reared under free-range conditions. For this aim, two hundred male chicks, 100 from fast-growing (Ross 308, R) and 100 from slow-growing (Naked Neck, NN) strain were farmed. At the end of the rearing period, at 81 days of age, 56 birds/strain were randomly selected for slaughtering and submitted to two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 40 publications
(40 reference statements)
1
11
0
Order By: Relevance
“…These findings are in line with those of Luton et al (2019), who reported poorer conditions of bulky broilers than those of a lighter weight strain. Shorter TI in RSG chickens is in line with findings of Mancinelli et al (2018), who reported shorter TI duration in Naked neck chickens than commercial fast-growing Ross broilers. Rural chickens are usually reared in free-range systems, have slower growth rate, and undergo harsh conditions during walking on abrasive ground.…”
Section: Resultssupporting
confidence: 88%
“…These findings are in line with those of Luton et al (2019), who reported poorer conditions of bulky broilers than those of a lighter weight strain. Shorter TI in RSG chickens is in line with findings of Mancinelli et al (2018), who reported shorter TI duration in Naked neck chickens than commercial fast-growing Ross broilers. Rural chickens are usually reared in free-range systems, have slower growth rate, and undergo harsh conditions during walking on abrasive ground.…”
Section: Resultssupporting
confidence: 88%
“…Some of our papers indicated [ 45 , 46 ] that the SG strains adopted in ERS could have a different response to the slaughtering process and thus different meat products would result. In this view, two other studies analyzed the effect of transport on welfare traits, several haematological parameters, in vivo oxidative status, carcase hygiene, and breast meat characteristics in two different chicken genotypes (FG and SG strains) reared under free-range conditions.…”
Section: Logisticalmentioning
confidence: 99%
“…The same consideration was not so for Salmonella spp., as different authors reported no shedding animals and no positive carcasses in PPP systems and MPPUs, respectively [47,62].…”
Section: Qualitative and Sanitary Implicationsmentioning
confidence: 99%
“…Our previous results [47] suggest that a 4-h journey to the slaughterhouse, compared to immediate slaughter in a MPPU, negatively affects some animal welfare traits (tonic immobility, creatine kinase, heterophil/lymphocyte ratio, lysozymes, reactive oxygen species, glucose and haptoglobin) in free-range chickens. The slow-growing chickens showed the highest susceptibility to stress, even with a greater antioxidant defence due to their foraging behaviour.…”
Section: Animal Welfare Aspectsmentioning
confidence: 99%
See 1 more Smart Citation